2020
DOI: 10.9734/cjast/2020/v39i1830769
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence and Variability Studies for Yield and Quality Traits in Elite Rice (Oryza sativa L.) Genotypes

Abstract: Genetic divergence and variability was assessed among 33 elite germplasm lines which were evaluated in RBD at Regional Agricultural Research Station, Warangal with an objective to classify  and understand the nature and magnitude of genetic diversity and variability  with regard to grain yield, yield components and quality traits using Mahalanobis D2 statistics. Genotypes were grouped into eight clusters and cluster I was the largest comprised of 23 genotypes followed by cluster II which consists of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
10
7
0
Order By: Relevance
“…Therefore the ninety one (91) genotypes categorized into ten (10) clusters is an indication of presence of high amount of genetic diversity in the germplasm. Here clustering was not based on any specific pattern of the crop with respect to origin, similar observation was also recorded in previous reports on rice (Mohanty et al, 2010; Devi et al, 2020) [8,10] . In the present study a considerable amount of genetic diversity was found among the germplasm lines which suggested that these diverse lines may serve as good source for selecting parents in hybridization programmes with an object to identify desirable segregants with respect to grain yield and other yield related traits.…”
Section: Genetic Divergence Analysissupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore the ninety one (91) genotypes categorized into ten (10) clusters is an indication of presence of high amount of genetic diversity in the germplasm. Here clustering was not based on any specific pattern of the crop with respect to origin, similar observation was also recorded in previous reports on rice (Mohanty et al, 2010; Devi et al, 2020) [8,10] . In the present study a considerable amount of genetic diversity was found among the germplasm lines which suggested that these diverse lines may serve as good source for selecting parents in hybridization programmes with an object to identify desirable segregants with respect to grain yield and other yield related traits.…”
Section: Genetic Divergence Analysissupporting
confidence: 89%
“…In the present study a considerable amount of genetic diversity was found among the germplasm lines which suggested that these diverse lines may serve as good source for selecting parents in hybridization programmes with an object to identify desirable segregants with respect to grain yield and other yield related traits. Similar study was conducted to isolate desirable segregants (Chandramohan et al, 2016; Devi et al, 2019) [2,10] . Reports (Murthy and Arunachalam., 1966; Devi et al, 2020) [7,10] has found out that as compare with geographic distance, genetic drift and selection in environment leads to more diversity.…”
Section: Genetic Divergence Analysismentioning
confidence: 91%
See 3 more Smart Citations